Wildlife trade at Belén and Modelo market, Peru: defining a baseline for conservation monitoring - D’Cruze, Neil; Elwin, Angie; Perez-Peña, Pedro E.; Vieto, Roberto; Asfaw, Alexander Eyob; Harrington, Lauren A. (Frontiers in Conservation Science, 2024)
Introduction Domestic wildlife markets have important nutritional, medicinal, cultural, and financial significance for local communities, but the scale and diversity of wildlife trade that passes through them is also associated with negative impacts on biodiversity, poor animal welfare, and potential human health risk. To design, and monitor the effectiveness of, interventions to ameliorate such impacts, an understanding of the species sold at the markets and their purpose is required, together with a robust (and potentially flexible) baseline. Here we focus on Belén (the largest open wildlife market in the Peruvian Amazon) and Modelo market, in Iquitos, Peru. Methods We surveyed wildlife products for sale at both markets approximately weekly over a year, using two different survey methods (open and discreet). To provide a baseline to support future conservation monitoring, we estimated a number of different market metrics (including indices of product availability, volume (observed per survey), and price), for the most frequently observed species ‘groups’, and compared indices of trade volume with daily river water levels. To provide a complete understanding of the range of species involved, we also described all threatened species recorded at the markets, the products sold, and their uses, including those that were only observed occasionally. Results Both markets sold predominantly wild meat, and some pets; at Belén Market >30% observations were of decorative, spiritual, or medicinal products. At least 71 unique species (including mammals, reptiles, birds, and invertebrates) were observed in total. The most frequently observed species ‘groups’ were: lowland paca, peccaries, caiman, river turtles, boas, yellow footed tortoise, parrots, and brocket deer. 27.7% of species were threatened or Near Threatened globally or nationally but there was no evidence that discreet surveys increased their detection. Daily river water levels were positively correlated with indices of trade volume for lowland paca, caiman, and yellow-footed tortoise, and negatively correlated with indices of trade volume for parrots and river turtle eggs. Discussion Beyond providing a comparative dataset, and insights regarding the apparent availability and value of a diversity of products (including food items, live pets, and other decorative, spiritual, and medicinal items), we suggest that simulations using these data could be used to optimize future monitoring efforts. Finally, our observations of correlations of per survey trade volumes of some species with daily river water levels in Iquitos may inform optimal time of year for species- specific surveys.